Hubungan Pola Asuh dan Status Gizi Balita Dengan Angka Kejadian Diare di Ruang Nusa Indah Bawah RSUD dr. Slamet Garut - Wahyudin Wahyudin; Andhika Lungguh Perceka (STIKes Karsa Husada Garut, 2019)
The factors affecting diarrhea are factors of bacterial, viral, and parasitic infections, Alabsorbsi, food, psychological, environmental conditions. In the developing country per year the average child has diarrhea 3-4 times the incident. The host factor is a nutrient condition, mother's foster pattern, hygiene behaviour. Nutritional intake depends on the social process that mothers do. Family interactions especially mothers and children are called parenting patterns. PEnelitianaims to find the relationship of foster care and nutritional Status of toddlers with the incidence OF diarrhea in the room Nusa Indah under the Dr. Slamet Garut hospital. Researchs methods used descriptive correlational, sample count of 62 respondents, data retrieval carried out with questionnaires. The results of the study of most of the mother's foster pattern is ineffective and most of the nutritional status of the toddler patient skinny category in the space Nusa Indah under the Dr. Slamet Garut hospital. Conclusion between the mother's foster pattern there is a connection with the incidence of diarrhea and among the nutritional status of children there is a relationship with diarrhea incidence rate in Nusa Indah AREA under the hospital Dr. Slamet Garut hospital. It is recommended to provide health education to the patient family about the foster pattern and the nutrition treatment in children to avoid diarrhea